Normal variations of coeliac and hepatic artery blood supply to the liver as identified on multidetector computed tomography (MDCT) studies at Groote Schuur Hospital, Western Cape Province, South Africa between 2018 and 2019 - Muzenda, Vengesai (Division of Radiology, 2021)
Background: Variant anatomy of the coeliac axis and hepatic arterial system is not uncommon and with the evolution of new minimally invasive surgical techniques and endovascular hepatic therapies, the interventional radiologist should have a good knowledge of the normal and variant anatomy to optimize treatment and minimise iatrogenic liver injuries. Objectives: To analyse, describe and illustrate the prevalence of the normal and variant anatomy of the coeliac axis and hepatic arterial system. Methods: A total of 300 MDCT angiography studies performed during a two-year period at Groote Schuur Hospital, Western Cape Province, South Africa were retrospectively reviewed to assess for the normal and variant anatomy of the coeliac axis and hepatic arterial system. Results: The CA and HA variations were analysed as per criteria by Uflacker's and modified Michel's respectively. The normal CA was seen in 88.3% (n=265). Most common variant anatomy was the hepatosplenic trunk seen in 2% (n=6). The remaining 3% (n=9) of patients were unclassified. Normal HA was seen in 55% (n=165). The most common variant anatomy was the accessory LHA seen in 12.7% (n=38). Classified HA variant anatomy was 30.7% and the remaining 14.3 % were unclassified. Double hepatic artery (2.7%) and CHA trifurcations (5.3%) were very common variants. Novel variants such as CHA off the SMA in combination with another variant in the form of accessory LHA (0.7%; n=2), combined double hepatic artery with an accessory LHA (0.3%; n=1) as well as accessory LGA off the PHA (0.3%; n=1) were identified. Conclusion: Variant coeliac axis and hepatic arterial anatomy is very common. Our population study demonstrated a greater prevalence of an accessory LHA than that reported in the literature. Although the rest of the variant frequencies were comparable to literature studies cited, novel hitherto undescribed variants were identified which the radiologist and hepatic surgeons need to be aware of. Two such variants were a persistent communication between SMA and CHA, and an accessory left gastric artery off the PHA.